Method for detecting homocysteine by using nano-pore sensor based on silver-sulfur polymerization

Through a nanopore sensor based on silver sulfur polymerization, DMACA is used to eliminate Cys interference and amplify the current signal changes, the Cys interference problem in Hcy detection in the prior art is solved, and the fast, simple, accurate and low-cost detection of Hcy is achieved, with excellent selectivity and anti-interference.

CN119643651AActive Publication Date: 2025-03-18CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202510091832.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art has Cys interference problems in selective detection of homocysteine ​​(Hcy), and the detection method is complex, time-consuming and cost-effective.

Method used

Using a nanopore sensor based on silver sulfur polymerization, the reaction differences between 4-dimethylaminocinnamaldehyde (DMACA) and Cys and Hcy are eliminated, and the current signal changes are amplified through the Ag(I) probe and special nanopore structure to achieve fast, simple, accurate and low-cost detection of Hcy.

Benefits of technology

High selectivity and specific response to Hcy are achieved, with the lower detection limit up to 1 μmol/L and the linear response range is 1 μmol/L to 30 μmol/L. It is suitable for Hcy detection in complex serum samples, with excellent selectivity and anti-interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643651A_ABST
    Figure CN119643651A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting homocysteine by a nano-pore sensor based on silver-sulfur polymerization, which comprises the following steps: pretreating a solution containing the homocysteine by 4-dimethylamino cinnamyl aldehyde, and then putting a sensor with a cylindrical nano-pore structure into the solution containing the homocysteine to carry out polymerization reaction; establishing a linear equation of the ratio of the conductivity before and after the polymerization reaction and the concentration of the homocysteine, and calculating the concentration of the homocysteine in the liquid to be detected through the linear equation. The liquid to be detected contains homocysteine and cysteine, and is pretreated by 4-dimethyl amino cinnamyl aldehyde before detection; and an Ag (I) probe is modified in a cylindrical nanopore channel of the sensor. According to the method, a special pretreatment method is utilized to cooperate with a constructed functional probe and a special nanopore structure, and current signal change is amplified based on silver-sulfur polymerization reaction, so that rapid and accurate detection of Hcy is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical / biological sensing, and in particular relates to a method for selectively detecting homocysteine ​​using a nanopore sensor based on Ag(Ⅰ)-thiol coordination polymer. Background Art

[0002] Homocysteine ​​(Hcy) is a thiol-containing amino acid. Hcy is usually produced by demethylation of methionine in the human body and decomposed into cysteine ​​(Cys) through transsulfurization. As an important biological thiol, Hcy is involved in many important physiological processes in the human body and is an important indicator. In normal human blood, the content of Hcy is 5μmol / L~15μmol / L. Maintaining a normal Hcy content helps the human body maintain a good biochemical balance. Excessive Hcy concentration in human blood is called hyperhomocysteinemia, but due to its complex structure and susceptibility to interference from other amino acids, the development of a fast, simple and accurate Hcy detection method is of great significance in the field of life analysis research. At present, the analytical methods for quantitative detection of Hcy mainly include high performance liquid chromatography-mass spectrometry tandem (HPLC-MS), gas chromatography-mass spectrometry (GC-MS), capillary electrophoresis, ion exchange chromatography, etc. These methods have disadvantages such as long detection time, complex sample preparation procedures, high detection cost, and expensive detection instruments. Therefore, the development of a fast, simple, accurate, and low-cost Hcy detection method has attracted widespread attention.

[0003] Compared with the above-mentioned sensors, the bionic nanopore sensor inspired by ion channels has the advantages of small detection restriction, excellent specificity and high sensitivity, and has greater application potential in the selective detection of Hcy.

[0004] Since Hcy and Cys have similar structures, Cys will interfere with the detection of Hcy, and this problem has not been well solved when the nanopore analysis sensors currently used detect Hcy, especially whether the interference of Cys can be effectively avoided and Hcy can be detected with high selectivity.

[0005] Therefore, it is crucial to establish a highly selective detection method for homocysteine. To date, there has been no report on the bionic nanopore analytical sensing method for selective detection of Hcy based on the reaction of DMACA with Cys, which effectively avoids the influence of Cys detection interference. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a method for detecting homocysteine ​​by a nanopore sensor based on silver-sulfur polymerization. The method utilizes the reaction difference between 4-dimethylaminocinnamaldehyde and Cys and Hcy, and eliminates the interference of the thiol group of Cys on the detection of Hcy through a cyclization reaction. At the same time, the current signal change is amplified based on the silver-sulfur polymerization reaction through the constructed functional probe and the special nanopore structure, thereby realizing rapid, simple, accurate and low-cost detection of Hcy.

[0007] In order to achieve the above technical objectives, the present invention provides a method for detecting homocysteine ​​using a nanopore sensor based on silver-sulfur polymerization, the method comprising the following steps:

[0008] 1) After a solution containing homocysteine ​​is pre-treated with 4-dimethylaminocinnamaldehyde, a sensor having a cylindrical nanopore structure is placed in the solution containing homocysteine ​​for polymerization reaction, and a linear equation of the ratio of conductivity before and after the polymerization reaction and the concentration of homocysteine ​​is established; the cylindrical nanopore of the sensor is modified with an Ag(Ⅰ) probe;

[0009] 2) replacing the solution containing homocysteine ​​with the test solution, measuring the ratio of the conductivity before and after the polymerization reaction, and then substituting the ratio into a linear equation to calculate the concentration of homocysteine ​​in the test solution; the test solution contains homocysteine ​​and cysteine.

[0010] The detection method of the present invention has an excellent effect of high selectivity and specific response for Hcy, which is based on the combined effect of a special pretreatment method and a polymerization reaction with the sensor to amplify the change of the current signal. Specifically, the structures of the detection objects Hcy and Cys are similar and difficult to distinguish, and the present invention uses 4-dimethylaminocinnamaldehyde (DMACA) to pre-treat the detection object, DMACA reacts with Cys to generate a stable five-membered heterocycle, and after the ring formation, the -SH of Cys becomes -S-, and DMACA reacts with Hcy, and it is not easy to generate a six-membered heterocycle, so the ring formation reaction eliminates the influence of the sulfhydryl group of Cys, and the -SH of Hcy-DMACA obtained by the reaction of Hcy with DMACA is retained, and this group undergoes a coordination polymerization reaction with the Ag (I) probe in the sensor, so as to accurately identify Hcy in the nanopore analysis sensing platform. The sensor of the present invention which is modified with Ag(I) probe and has a cylindrical nanopore structure, when Hcy-DMACA enters the pore, utilizes the supramolecular interactions such as metal-ligand interaction and metal-metal interaction between Ag(I) and thiol compounds to form an Ag(I)-thiol coordination polymer with Ag(I) as a node and thiol as a ligand, which occupies the effective diameter in the nanopore. The molecular chain is relatively long, and compared with the bare pore without fixed probe, it can significantly cause the change of current signal, thereby realizing the rapid quantitative detection of Hcy.

[0011] As a preferred solution, the cylindrical nanopore structure of the sensor is single-hole or multi-hole. The inventors found that when applied to the detection of Hcy, the sensor further using a single-hole cylindrical nanopore structure has higher selectivity and response value. The formation of a single hole or multi-hole is achieved by controlling the number of ions in the ion bombardment device. When multiple ions bombard the film, multiple ion tracks are formed, and a porous membrane can be obtained. By reducing the number of incident ions through the control device and stopping the bombardment immediately after an ion bombardment, a single ion track is formed, and a single nanopore can be prepared.

[0012] As a preferred solution, the sensor having a cylindrical nanopore structure is first modified with a cysteine ​​group in the pore, and then the Ag(I) probe is modified via an Ag-S bond.

[0013] As a preferred solution, the preparation of the sensor having a cylindrical nanopore structure comprises the following steps:

[0014] (1) After bombarding the PET film with heavy ions to form ion tracks inside the film, an ultraviolet lamp is used for activation treatment, and then the tracks of the PET film are symmetrically etched with sodium hydroxide to form a PET film with cylindrical nano-channels having through holes;

[0015] (2) The PET film having the through cylindrical nanopores is immersed in an activation solution containing EDC, NHS and MES, and then cysteine ​​is added for grafting modification to obtain a Cys / PET nanopore sensor;

[0016] (3) The Cys / PET nanopore sensor is immersed in a buffer solution containing AgNO3 to modify the Ag(I) probe via the Ag(I)-S bond to obtain the Ag(I) / Cys / PET nanopore sensor.

[0017] The principle of preparing the Ag(Ⅰ) / Cys / PET nanopore sensor of the present invention is that: since heavy ions have high energy, when heavy ions bombard the PET film, a damage track will be formed inside the PET film; and ultraviolet rays can excite the chemical bonds in the PET molecules and increase their reactivity. Since the chemical structure of the track area is different from that of the unbombarded area after heavy ion bombardment and ultraviolet activation, the reactivity to sodium hydroxide is enhanced. Sodium hydroxide will react chemically with the PET molecular chain, preferentially symmetrically etching the track area from both sides of the PET film synchronously, and gradually forming a cylindrical nanopore with a through hole. The PET pore after ion bombardment and symmetrical etching with alkaline solution has different physical and chemical properties from the rest of the PET film. Under alkaline conditions, the ester group in the PET pore reacts with the hydroxide ion, the ester bond breaks, and carboxylate and ethylene glycol are generated. The carboxylate is further hydrolyzed to obtain a carboxyl group, thereby covering a large number of carboxyl groups in the PET pore. Then, the carbodiimide chemical connection method was used to fix Cys on the inner surface of the cylindrical nanopore. The successfully modified Cys can modify the inner surface of the pore and cover a large number of thiol groups. The thiol introduced by Cys forms an Ag(Ⅰ)-S bond with Ag(Ⅰ) to fix the Ag(Ⅰ) probe on the inner surface of the Cys-modified nanopore. After the successful modification, the inner surface of the pore is modified again and covered with a large amount of Ag(Ⅰ).

[0018] As a preferred solution, the heavy ion is Xe.

[0019] As a preferred solution, the ultraviolet lamp irradiation time is 9 to 12 hours.

[0020] As a preferred solution, the symmetrical etching time is 4 to 10 minutes, and the temperature is 50 to 60°C. When the symmetrical etching time in the present invention is too short, not only will the channel not be penetrated, but the formed pore size will be small, resulting in the inability of the required fixed Cys and Ag (I) probes to enter and be unable to be detected, or the required Hcy to be detected to enter, making it difficult to complete the polymerization reaction; as the etching time increases, the diameter of the cylindrical nanopore will increase. If the pore size is too large, the changes in the effective diameter and conductivity of the channel will not be obvious, interfering with the detection results. More preferably, the symmetrical etching time is 8 to 10 minutes, and more preferably 10 minutes.

[0021] As a preferred solution, in step 2, the molar ratio of EDC, NHS, MES and cysteine ​​is 50:250:100:(8-10), the pH of the activation solution is 4.7-5.5, and the grafting modification time is 1-2 hours. Within the molar ratio range selected by the present invention, the carbodiimide chemical connection method can be used to successfully fix and modify Cys in the nanopores, ensuring the grafting rate of Cys.

[0022] As a preferred solution, in step 3, the molar ratio of AgNO3 to cysteine ​​is (1-1.5):1, the immersion time is 1-2 hours, and the immersion process is in a light-proof environment, and the buffer is a sodium acetate-acetic acid buffer with a pH of 5.0-5.5. Performing in a light-proof environment can effectively prevent Ag(I) from being reduced to metallic silver, thereby affecting the construction of the Ag(I) / Cys / PET nanopore sensor.

[0023] As a preferred scheme, the concentration of homocysteine ​​in the homocysteine-containing solution is 1 μmol / L to 30 μmol / L, and the linear equation is y=0.91-0.025x; wherein y is the ratio of the conductivity before and after the polymerization reaction, and x is the concentration of homocysteine, in μmol / L. The present invention defines the conductivity of the Ag(Ⅰ) / Cys / PET nanopore before the polymerization reaction as G0, and the conductivity of the Ag(Ⅰ) / Cys / PET nanopore after the polymerization reaction as G, and y equals G / G0. In the present invention, as the concentration of Hcy increases, G / G0 gradually decreases, and when the concentration of Hcy is greater than 35 μmol / L, G / G0 tends to stabilize. Within the concentration range of 1 μmol / L to 30 μmol / L, G / G0 has a good linear relationship with the corresponding Hcy concentration, and the correlation coefficient R 2 The detection limit is 0.99 and can reach 1μmol / L.

[0024] As a preferred solution, the polymerization reaction time is 30 to 80 minutes. As the polymerization reaction time of the present invention increases, the polymer in the nanopore slowly occupies the pore space, the ion concentration in the pore decreases, and the conductivity of the nanopore begins to decrease. When it increases to a certain extent, the volume of the polymer in the pore no longer increases, and the conductivity change rate tends to be stable. It is further preferred that the polymerization reaction time is 60 to 80 minutes.

[0025] As a preferred solution, the molar ratio of the solution containing homocysteine ​​to 4-dimethylaminocinnamaldehyde is 1:(1-1.2), wherein the solution containing homocysteine ​​is calculated based on homocysteine.

[0026] As a preferred solution, the selectivity and anti-interference of the Ag(Ⅰ) / Cys / PET nanopore analysis sensing platform were tested by using control samples of other amino acids and thiol compounds with 10 times the concentration.

[0027] As a preferred solution, the standard addition method is used for the detection in the actual pig serum sample. Different concentrations of Hcy are added to the treated pig serum for quantitative detection, and the anti-interference ability of the sensor in pig serum is examined.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The method of the present invention utilizes the reaction difference between 4-dimethylaminocinnamaldehyde and Cys and Hcy, eliminates the interference of the thiol group of Cys on the detection of Hcy through a cyclization reaction, and simultaneously amplifies the change of the current signal based on the silver-sulfur polymerization reaction through the synergistically constructed functional probe and the special nanopore structure, thereby realizing the rapid, simple, accurate and low-cost detection of Hcy.

[0030] 2) During the action of the sensor of the present invention, the Ag(Ⅰ)-Hcy-DMACA coordination polymer chain formed by coordination bond bonding can hinder the ion transmission in the pores by virtue of its volume effect, and the quantitative detection of Hcy is achieved by detecting the change of conductivity in the pores.

[0031] 3) The method of the present invention is based on the selective detection of homocysteine ​​by the Ag(Ⅰ)-thiol coordination polymer nanopore sensor, and realizes the quantitative detection of Hcy by detecting the change of conductivity. The linear response range of the Ag(Ⅰ) / Cys / PET nanopore sensor to Hcy is 1μmol / L to 30μmol / L, and the detection limit can reach 1μmol / L, which is lower than the normal Hcy content in the human body.

[0032] 4) The sensor of the present invention has excellent selectivity and anti-interference, and can be used for Hcy detection in complex serum samples. The method is used to detect Hcy in pig serum, with a recovery rate of 102.5% to 105.9% and a relative standard deviation RSD of 1.0% to 6.4%, which expands its application field.

[0033] 5) The method of the present invention has the advantages of simple device, high sensitivity, short time consumption and no labeling.

[0034] 6) The surface of the nanopore sensor prepared by etching PET as the substrate is covered with a large number of carboxyl groups, which is convenient for fixing various identification elements. At the same time, since PET material has good thermal stability and flexibility, PET nanopore sensors have great potential in the field of wearable sensing devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The schematic diagram of the construction of Ag(Ⅰ) / Cys / PET nanopore sensor and its selective detection of Hcy is shown in Figure 1. The schematic diagram of the cross section of PET is shown in Figure 2.

[0036] Figure 2SEM images of the surfaces at both ends of the cylindrical nanochannels prepared with different etching times in Example 2 (scale is 500 nm): the etching time for (A) and (E) is 4 min; the etching time for (B) and (F) is 6 min; the etching time for (C) and (G) is 8 min; the etching time for (D) and (H) is 10 min.

[0037] Figure 3 This is the XPS spectrum of the nanopore modification process in Example 1 (the black line is the unmodified nanopore; the red line is the Cys-modified nanopore; the blue line is the Ag(I) / Cys-modified nanopore).

[0038] Figure 4 (A) The IV curves of the Ag(Ⅰ) / Cys / PET nanopore before and after detecting Hcy-DMACA (A), Hcy (B), Cys-DMACA (C), Cys (D), and GSH (E) in Example 1; (F) The IV curve of the unmodified nanopore before and after detecting Hcy-DMACA.

[0039] Figure 5 The change of nanopore conductivity at different polymerization reaction times in Example 3.

[0040] Figure 6 (A) Effect of different Hcy concentrations on the conductivity change of Ag(Ⅰ) / Cys / PET nanochannels prepared in Example 1; (B) Linear relationship between conductivity change and Hcy concentration.

[0041] Figure 7 The response of the Ag(Ⅰ) / Cys / PET nanochannel prepared in Example 1 to different amino acids.

[0042] Figure 8 The responses of the Ag(I) / Cys / PET nanochannels prepared in Example 1 to Hcy and different thiol interferents, wherein Hcy refers to Hcy-DMACA treated with DMACA. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.

[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0045] The polyethylene terephthalate (PET) film (thickness of 13 μm, biaxial orientation) used in the embodiments of the present invention and the comparative examples was purchased from Goodfellow, Germany; the Ag / AgCl electrode was purchased from Shanghai Xianren Instrument Co., Ltd.; the experimental water was ultrapure water (resistivity ≥18.3 MΩ·cm); the reagents used were all analytical grade (AR), and in the following description, the description of amino acids uses English abbreviations.

[0046] Example 1

[0047] 1. Preparation of Ag(Ⅰ) / Cys / PET Nanopore Sensor

[0048] The cylindrical nanopores were prepared by ion track etching. The PET film was bombarded with a single heavy ion Xe (8.98 MeVu -1 ) to obtain a PET film with a single track, and then use a 312nm ultraviolet lamp to irradiate the PET film for activation treatment, irradiate the front side for 12h, and irradiate the back side for 9h. After the irradiation is completed, the PET film is immediately symmetrically etched with a 3mol / L NaOH solution, the etching temperature is 50°C, and the etching time is 10min to obtain a single-hole cylindrical hole. After the etching is completed, the surface of the PET film is cleaned with distilled water and left to stand in ultrapure water overnight.

[0049] Ag(Ⅰ) / Cys / PET nanopores were prepared by chemical modification. Cys has two functional groups, amino and thiol. Cys was fixed on the inner surface of the cylindrical nanopore by carbodiimide chemical connection method; Ag(Ⅰ) was fixed on the inner surface of the Cys-modified nanopore by Ag(Ⅰ)-S bond. First, MES solution (0.1mol / L, pH 4.7) mixed with 50mmol / L EDC and 250mmol / L NHS was placed in the dispersion tanks on both sides of the PET film. After soaking for 1h, the mixed solution was taken out and the dispersion tank was rinsed with ultrapure water. 8mmol / L Cys modification solution was prepared using 10mmol / L PBS buffer (pH7.4) and placed in the dispersion tanks on both sides of the PET film. After soaking for 1h, the Cys modification solution was taken out and the dispersion tank was rinsed with ultrapure water. Subsequently, 1mol / L NaF electrolyte solution was added to the dispersion tanks on both sides of the Cys-modified PET film, and the current-voltage (IV) curve was measured to detect whether Cys was successfully modified.

[0050] Secondly, 8mmol / L AgNO3 modification solution was prepared using 10mmol / L sodium acetate-acetic acid buffer (NaAc-HAc buffer) with a pH of 5.0 and placed in the dispersion grooves on both sides of the PET film. After soaking in the dark for 1 hour, the AgNO3 modification solution was taken out and the dispersion grooves were rinsed with ultrapure water. Subsequently, 1mol / L NaF electrolyte solution was added to the dispersion grooves on both sides of the PET film, and the IV curve was measured to detect whether Ag(Ⅰ) was successfully modified and whether Ag(Ⅰ) / Cys / PET nanopores were obtained.

[0051] 2.4-Dimethylaminocinnamaldehyde Pretreatment Method for Biothiols

[0052] Before the experiment, the biothiol needs to be pretreated. A series of concentrations (100mmol / L, 50mmol / L, 10mmol / L, 5mmol / L, 1mmol / L) of 4-dimethylaminocinnamaldehyde (DMACA) solution, Cys solution, Hcy solution and GSH (glutathione) solution were prepared using 0.1mol / L carbonate buffer at pH 9.5.

[0053] The DMACA solution was mixed with equal volumes of Hcy solution, Cys solution and GSH solution of the same concentration, respectively, and stirred at room temperature for 20 min to prepare Hcy-DMACA solution, Cys-DMACA solution and GSH-DMACA solution of a certain concentration, which were stored in a light-proof environment for subsequent experiments.

[0054] 3. Ag(Ⅰ)-thiol polymerization method

[0055] Take 10 μL of Hcy solution with a concentration of n mmol / L (n is determined according to experimental requirements) and 5 μL of AgNO3 solution with a concentration of 2n mmol / L, and add them into 2 mL of sodium acetate-acetate buffer (10 mmol / L, pH 5.0) in sequence. After shaking evenly, let it stand in the dark for 1 hour to obtain Ag(Ⅰ)-Hcy coordination polymer with Hcy and AgNO3 concentrations of both 5nμmol / L.

[0056] By repeating the above steps, Ag(Ⅰ)-Cys coordination polymer with Cys and AgNO3 concentrations of 5 nmol / L and Ag(Ⅰ)-Hcy-DMACA coordination polymer with Hcy-DMACA and AgNO3 concentrations of 5 nmol / L can be prepared.

[0057] 4. Detection of Hcy by Ag(Ⅰ) / Cys / PET nanopore sensor

[0058] The Ag(Ⅰ) / Cys / PET nanopore sensor achieves quantitative analysis of Hcy through the change of current signal. The dual-electrode system detects the current signal at both ends of the nanopore. 1 mol / L NaF electrolyte solution is added to the dispersion grooves on both sides of the PET film. Ag / AgCl electrodes and the It test function of the electrochemical workstation are used to measure the current signal on both sides of the pore under steady-state voltage, record the current size under different voltages, and draw an IV curve. By calculating the slope of the IV curve in the voltage range of -60mV to 60mV, the conductivity G0 of the nanopore before polymerization reaction can be obtained.

[0059] A series of Hcy concentrations (concentrations of 0.1 μmol / L, 1 μmol / L, 5 μmol / L, 10 μmol / L, 15 μmol / L, 20 μmol / L, 30 μmol / L, 35 μmol / L, 40 μmol / L, 60 μmol / L) sodium acetate-acetic acid solutions were prepared after DMACA treatment, and 200 μmol / L AgNO3 sodium acetate-acetic acid solutions were prepared using sodium acetate-acetic acid buffer with the same concentration and pH. 0.5 mL of 200 μmol / L AgNO3 sodium acetate-acetic acid solution was added to the dispersion tank on the left side of the nanopore, and 1.0 mL of the prepared Hcy sodium acetate-acetic acid solution with a series of concentrations treated with DMACA was added to the right side of the dispersion tank, and the solution was kept in the dark for 1 hour. After the polymerization reaction was completed, the solution on both sides of the dispersion tank was sucked out, and the electrolytic cell was cleaned with ultrapure water. The current signal was detected, and the conductivity G of the nanopore after the polymerization reaction was completed was calculated. The conductivity of the Ag(Ⅰ) / Cys / PET nanopore before the polymerization reaction was defined as G0, and the ratio of the conductivity before and after the nanopore polymerization reaction G / G0 was used to reflect the change in nanopore conductivity. At the same time, by exploring the relationship between G / G0 and Hcy concentration, the response performance of the Ag(Ⅰ) / Cys / PET nanopore sensor to Hcy was evaluated.

[0060] Furthermore, this method was used to evaluate the selectivity of Ag(Ⅰ) / Cys / PET nanopore sensor for Hcy.

[0061] Later, pig serum was used, and the supernatant was taken after treatment. The standard addition method was used, and 100 μL of 1mmol / L DMAC solution and 100 μL of Hcy (concentrations of 5, 10, 15, 20 μmol / L) and Cys (concentration of 100 μmol / L) mixed solution were added. After shaking, the pH of the solution was adjusted to 9.5 with NaOH, and then stirred at room temperature for 20 minutes. Take 500 μL of the above DMACA-treated serum sample, mix it evenly with 500 μL 10mmol / L acetate buffer (pH5.0), and adjust the pH to 5.0 with sodium acetate. The subsequent experimental process is consistent with the above description.

[0062] The sensor prepared in Example 1 was tested:

[0063] 1) XPS spectrum characterization of nanopore modification process

[0064] X-ray photoelectron spectroscopy (XPS) was used to characterize the modification process of Ag(Ⅰ) / Cys / PET nanopore sensor. Figure 3 . In the unmodified cylindrical nanopore (black line), only the O1s and C1s peaks are clearly visible, which are the O and C elements contained in the PET substrate material itself. After the cylindrical nanopore is modified with Cys (red line), the N 1s peak (near 399eV) is clearly visible, and the introduction of the N element can prove the successful modification of Cys. After the cylindrical nanopore is further modified with AgNO3 (blue line), the Ag 3d peak near 370eV is clearly visible, and the Ag element is introduced into the nanopore, which proves the successful modification of Ag(Ⅰ) in the nanopore.

[0065] 2) Electrochemical performance test

[0066] The behavior of Ag(Ⅰ) / Cys / PET nanopores on the ionic current and conductivity of three biothiols, Hcy, Cys, and GSH, after treatment with DMACA was investigated. Figure 4 As shown in (C) and (D), after Cys is added to the Ag(Ⅰ) / Cys / PET nanopores, it will also undergo coordination polymerization with Ag(Ⅰ) in the pores to form polymers due to its thiol group. After DMACA treatment, Cys undergoes a cyclization reaction ( Figure 1 ) generates Cys-DMACA and loses the thiol group. After being added into the Ag(Ⅰ) / Cys / PET nanopores, it does not undergo coordination polymerization reaction with Ag(Ⅰ), no polymer is generated in the pores, and the pore conductivity does not change significantly.

[0067] GSH cannot coordinate with Ag(Ⅰ) to form a coordination polymer at pH 5.0. Figure 4 As shown in (E), after GSH was added to the Ag(Ⅰ) / Cys / PET nanopores, the conductivity of the nanopores did not change significantly. In order to verify the fixation effect of Ag(Ⅰ) modified on the inner surface of the nanopores on the coordination polymer, Figure 4 As shown in (F), after Hcy-DMACA and Ag(Ⅰ) were added to the unmodified nanopores, the conductivity of the nanopores did not change significantly, indicating that if the polymer cannot be fixed in the nanopores after generation, it will be discharged from the nanopores along with the solution, and will not cause significant changes in the ionic current and conductivity of the nanopores.

[0068] 3) Linear range and detection limit

[0069] A series of Hcy solutions were prepared, and the Ag(Ⅰ) / Cys / PET nanopore sensor was used to quantitatively analyze Hcy. In the experiment, G / G0 was used to reflect the change of nanopore conductivity. The experimental results are shown in Figure 6 As shown in (A), with the increase of Hcy concentration, G / G0 gradually decreases, and when the Hcy concentration is greater than 35 μmol / L, G / G0 tends to be stable. Figure 6 As shown in (B), within the concentration range of 1 μmol / L to 30 μmol / L, G / G0 and the corresponding Hcy concentration showed a good linear relationship, the linear equation y = 0.91-0.025x (μmol / L), and the correlation coefficient R 2 The detection limit is 0.99 and can reach 1μmol / L.

[0070] 4) Selective testing

[0071] The selectivity of the sensor was studied by examining the polymerization of different amino acids and biothiols in the Ag(Ⅰ) / Cys / PET nanopores. Cysteine ​​(Cys), cystine (cystine), methionine (Met), arginine, glutamic acid, alanine, proline, glycine, aspartic acid, tyrosine, leucine, tryptophan, serine, threonine, valine, lysine, histidine, and glutathione (GHS) were selected as controls, and their concentrations were 10 times greater than that of the Hcy solution. The conductivity of the sensor with modified probes but no polymerization reaction was used as the control group. Figure 7 As shown in the figure, only in the presence of Hcy, the pore conductivity decreased significantly, and the other 18 control substances could not undergo coordination polymerization with Ag(Ⅰ) in the pore after treatment, and the pore conductivity did not change significantly. Therefore, the Ag(Ⅰ) / Cys / PET nanopore sensor has excellent selectivity for Hcy.

[0072] 5) Anti-interference test

[0073] The experiment selected cysteine, glutathione, methionine (Met), and cystine as interfering substances, and their concentrations were 10 times greater than that of the Hcy solution. The interfering substance solution was mixed with the Hcy solution. Figure 8 As shown in the figure, the pore conductivity decreased significantly after adding Hcy treated with DMACA and different interferents, and the conductivity ratio G / G0 before and after the polymerization reaction was basically consistent with the conductivity ratio after the polymerization reaction of only adding Hcy solution treated with DMACA into the pore. Therefore, the Ag(Ⅰ) / Cys / PET nanopore sensor has excellent anti-interference ability for the detection of Hcy.

[0074] 6) Actual sample testing and recovery rate determination

[0075] The application of Ag(Ⅰ) / Cys / PET nanopore sensor in actual sample detection was investigated, and Hcy in porcine serum samples was detected. Different concentrations of Hcy were added to the treated porcine serum for quantitative detection, and 100 μmol / L Cys was added to the porcine serum to interfere with the detection. The test showed that the recovery rate of Hcy was 102.5% to 105.9%, and the relative standard deviation RSD was 1.0% to 6.4%. The spiked recovery rate and relative standard deviation were both within a reasonable range. Therefore, the Ag(Ⅰ) / Cys / PET nanopore sensor can be used for Hcy detection in complex serum samples.

[0076] Example 2

[0077] The effect of different etching times on the sensor pore size was investigated. The cylindrical nanopores were prepared by ion track etching. The PET film was bombarded with multiple heavy ions Xe (8.98 MeVu -1 ) to obtain a PET film with multiple tracks, and then use a 312nm ultraviolet lamp to irradiate the PET film for activation treatment, irradiate the front side for 12h, and irradiate the back side for 9h. After the irradiation is completed, the PET film is immediately symmetrically etched with a 3mol / L NaOH solution. The etching temperature is 50°C, and the etching time is 4min, 6min, 8min and 10min respectively, to obtain porous cylindrical channel PET films with different pore sizes. After the etching is completed, the surface of the PET film is cleaned with distilled water and allowed to stand in ultrapure water overnight. The cylindrical channel PET film was characterized by SEM, such as Figure 2 shown.

[0078] Scanning electron microscopy (SEM) was used to characterize the nanopores on the left and right ends of the cylindrical nanopore PET film at 4min, 6min, 8min, and 10min. Figure 2 The pore size increases with the increase of etching time. The pore size at both ends of the cylindrical nanopore with an etching time of 4 min is about 63.1 nm, the pore size at both ends of the cylindrical nanopore with an etching time of 6 min is about 109.5 nm, the pore size at both ends of the cylindrical nanopore with an etching time of 8 min is about 158.7 nm, and the pore size at both ends of the cylindrical nanopore with an etching time of 10 min is about 201.3 nm. Based on the space effect within the pore, the cylindrical nanopore with an etching time of 10 min is further preferred to construct the Ag(Ⅰ) / Cys / PET nanopore sensor.

[0079] Example 3

[0080] The difference between this embodiment and embodiment 1 is that the polymerization reaction time is replaced with 30min, 40min, 50min, 70min and 80min respectively, and the other steps and conditions are the same. The effect of the polymerization reaction time of Hcy in the sensor channel on the change of conductivity is investigated. The results are as follows: Figure 5 shown.

[0081] The results show that when the reaction time is 30 minutes, the polymer in the nanopore occupies the pore space, the ion concentration in the pore decreases, and the conductivity of the nanopore begins to decrease. When the polymerization reaction time is 60 minutes, the conductivity change rate tends to be stable, which indicates that the volume of the polymer in the pore no longer increases. The optimal coordination polymerization reaction time in the pore is 60 minutes.

[0082] The above results show that the present invention constructs an Ag(Ⅰ) / Cys / PET nanopore sensor for the selective detection of Hcy based on the Ag(Ⅰ)-thiol coordination polymerization reaction. The Ag(Ⅰ)-thiol coordination polymerization reaction was explored using characterization methods. Since Ag(Ⅰ) can undergo coordination polymerization with thiol to generate coordination polymers, Hcy treated with 4-dimethylaminocinnamaldehyde is added to the Ag(Ⅰ) / Cys / PET nanopore to generate Ag(Ⅰ)-Hcy-DMACA coordination polymers, which hinder the ion transmission in the pores and reduce the conductivity of the pores. The quantitative detection of Hcy is achieved by detecting the change in conductivity. The linear response range of the Ag(Ⅰ) / Cys / PET nanopore sensor to Hcy is 1μmol / L to 30μmol / L, and the detection limit can reach 1μmol / L, which is lower than the normal Hcy content in the human body. At the same time, the sensor has excellent selectivity and anti-interference, is not easily interfered by other amino acids and biological thiols during the detection process, and can be used for Hcy detection in complex serum samples. In addition, the sensor has the advantages of low manufacturing cost, batch production, simple operation, no need for large instruments, and fast detection time of only 90 minutes. It is a biosensor platform with great potential.

Claims

1. A method for detecting homocysteine ​​based on a silver-sulfur polymerized nanopore sensor, characterized in that: The following steps are involved: 1) After a solution containing homocysteine ​​is pre-treated with 4-dimethylaminocinnamaldehyde, a sensor having a cylindrical nanopore structure is placed in the solution containing homocysteine ​​for polymerization reaction, and a linear equation of the ratio of conductivity before and after the polymerization reaction and the concentration of homocysteine ​​is established; the cylindrical nanopore of the sensor is modified with an Ag(Ⅰ) probe; 2) replacing the solution containing homocysteine ​​with the test solution, measuring the ratio of the conductivity before and after the polymerization reaction, and then substituting the ratio into a linear equation to calculate the concentration of homocysteine ​​in the test solution; the test solution contains homocysteine ​​and cysteine.

2. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 1, characterized in that: The sensor with a cylindrical nanopore structure is prepared by first modifying a cysteine ​​group in the pore, and then modifying an Ag(I) probe through an Ag-S bond.

3. The method for detecting homocysteine ​​based on a silver-sulfur polymerization nanopore sensor according to claim 2, characterized in that: The preparation of the sensor having a cylindrical nanopore structure comprises the following steps: (1) After bombarding the PET film with heavy ions to form ion tracks inside the film, an ultraviolet lamp is used for activation treatment, and then the tracks of the PET film are symmetrically etched with sodium hydroxide to form a PET film with cylindrical nano-channels having through holes; (2) The PET film having the through cylindrical nanopores is immersed in an activation solution containing EDC, NHS and MES, and then cysteine ​​is added for grafting modification to obtain a Cys / PET nanopore sensor; (3) The Cys / PET nanopore sensor is immersed in a buffer solution containing AgNO3 to modify the Ag(I) probe via the Ag(I)-S bond, thereby obtaining an Ag(I) / Cys / PET nanopore sensor.

4. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 3, characterized in that: The ultraviolet light irradiation time is 9 to 12 hours; The symmetrical etching time is 4 to 10 minutes, and the temperature is 50 to 60°C.

5. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 3 or 4, characterized in that: In step 2, the molar ratio of EDC, NHS, MES and cysteine ​​is 50:250:100:(8-10), the pH of the MES activation buffer solution is 4.7-5.5; and the grafting modification time is 1-2 hours.

6. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 5, characterized in that: In step 3, the molar ratio of AgNO3 and cysteine ​​is (1-1.5):1, the immersion time is 1-2 hours, and the immersion process is kept in a light-proof environment, and the buffer solution is a sodium acetate-acetic acid buffer solution with a pH of 5.0-5.

5.

7. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 1, characterized in that: The concentration of homocysteine ​​in the homocysteine-containing solution is 1 μmol / L to 30 μmol / L, and the linear equation is y=0.91-0.025x; wherein y is the ratio of the conductivity before and after the polymerization reaction, and x is the concentration of homocysteine ​​in μmol / L.

8. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 7, characterized in that: The polymerization reaction time is 30 to 80 minutes.

9. The method for detecting homocysteine ​​using a silver-sulfur polymerization nanopore sensor according to claim 7, characterized in that: The molar ratio of the solution containing homocysteine ​​to 4-dimethylaminocinnamaldehyde is 1:(1-1.2), wherein the solution containing homocysteine ​​is calculated based on homocysteine.

Citation Information

Patent Citations

  • Method for rapidly and accurately detecting homocysteine in urine

    CN113267550A

  • Method for detecting homocysteine in urine by using enzyme modified electrode

    CN113267551A

  • Method for measuring cysteine, homocysteine and glutathione

    CN114088676A

  • Nanoprobe for specifically detecting cysteine in organism and application of nanoprobe

    CN116925756A

  • Colorimetric and Fluorometric Determination of Homocysteine and Cysteine

    US20080261315A1

Cited By

  • 4-APM / Zr-MOF / PET nano-pore sensor based on spatial modification and preparation method and application of 4-APM / Zr-MOF / PET nano-pore sensor

    CN122306906A